Training Model to Increase a Kick Speed in Pencak Silat Athletes 15-17 Years Age in Sanga Village District - Ilahi, Tri Wahyuni; Noviria Sukmawati; Selvi Melianty; Martinus, Martinus (UNIB Press, 2024)
Straight kicks are often used to gain points when facing each other. To perform a good straight kick, there is an element of physical condition needed to carry out this movement to support the execution of the movement properly and correctly. The aim of this research was to increase the speed of A pencak silat kicks in athletes aged 15-17 years in Sanga Village. This research method uses the development of the ADDIE model using 5 stages, namely analysis, design, development, implementation and evaluation (ADDIE). The research subjects consisted of 30 athletes. The research instrument used an assessment scale by 3 experts, namely pencak silat experts, movement experts and martial arts experts. The results of the research using the expert validation test Content Validity Index (CVI) and Content Validity Ratio (CVR) on the Kick Training Model A with an average CVR value of -0.05 means that the training model to increase the speed of kick A in pencak silat has validity high so that the A pencak silat kick training model is safe to use, according to the characteristics of athletes aged 15-17 years.